Mobile assisted language learning : concepts, contexts and challenges - Stockwell, Glenn (Cambridge CUP, 2022)
"The increased use of sophisticated mobile devices opens up new possibilities and challenges for language teachers and learners, which has led to an increasing need to consider issues relating to mobile technologies specifically. To date, there is no comprehensive book-length treatment of issues relating to Mobile Assisted Language Learning (MALL). This book fills that gap, providing a resource for present and future language teachers, and for graduate students of applied linguistics and TESOL, to understand how mobile devices can best be used for language teaching. It is founded on existing research, practice, and theory, and offers a balanced perspective, based on the author's own experiences with mobile learning, considering the limitations of such an approach, as well as the benefits. Written in a practical and approachable tone, it provides a much-needed guide to MALL, and its fascinating insights with promote further debate within the field"--
Includes bibliographical references and index.
Keywords: Mobile-assisted language learning; Mobile communication systems in education; LANGUAGE ARTS & DISCIPLINES / Linguistics / General